Detection of Crimean-Congo hemorrhagic fever virus and Rift Valley fever virus antibodies in animal workers in Cameroon - Machuetum, Gisele Liliane; Tchatchueng-Mbougua, Jules Brice; Munyeku-Bazitama, Yannick; Mizuma, Keita; Essima, Gael; Mounchili, Landry; Nsangou, Christian Yogne; Owona, Jean Dominique Mbarga; Djuicy, Delia Doreen; Yonga, Martial; Souleymanou, Maloum; Poueme, Rodrigue; et al. (Frontiers in Veterinary Science, 2025)
IntroductionCrimean-Congo hemorrhagic fever virus (CCHFV) and Rift Valley fever virus (RVFV) are emerging arboviruses primarily affecting domestic animals. Research has demonstrated their endemicity in various parts of the world, including Africa. Despite the high seroprevalence of CCHFV infection recently reported among cattle in Cameroon, the epidemiological status of animal workers who frequently interact with these animals remains poorly understood. This study investigates the seroprevalence of CCHFV and RVFV infections, along with associated factors, among animal workers in Cameroon.MethodsBetween May 2023 and January 2024, blood samples were collected from shepherds, slaughterers, butchers, and veterinarians at farms, slaughterhouses, and livestock markets in Centre and North regions in Cameroon. Serum samples were analyzed for Immunoglobulin G (IgG) antibodies against CCHFV and RVFV using the enzyme-linked immunosorbent assay (ELISA) and neutralization tests. Univariate and multivariable analyses were conducted using R statistical software version 4.1.ResultsSeroprevalence estimates of CCHFV and RVFV among high-risk population were 4.6% (36/790) and 9.9% (78/790), respectively. Multivariable analysis revealed that participants with 21–40 years or more than 41 years of professional experience were significantly associated with higher RVFV seroprevalence [aOR = 2.31; 95% CI: 1.02–5.23 and aOR = 5.34; 95% CI: 1.84–15.58, respectively] compared to those with 1–5 years of experience, suggesting that RVFV seroprevalence increases with longer employment duration. None of the variables analyzed were associated with CCHFV occurrence.DiscussionOur study confirms the presence of CCHFV and RVFV antibodies among animal workers. These viruses are likely endemic in Cameroon, despite the absence of reported clinical cases. We recommend implementing regular surveillance and preventive measures to protect at-risk populations.